Testing for the stability and persistence of the Phillips curve for Nigeria - Chuku Chuku; Johnson Atan; Felix Obioesio (CBN Journal of Applied Statistics, 2017)
In this study, we describe the problem of testing for the stability and persistence of the Phillips curve for Nigeria when there are nonstationarities in the marginal distribution of the regressors. We test for unknown break dates using the SupF, AvgF and ExpF approaches. After reviewing the relevant asymptotic distribution theory we replicate Hansenfs fixed-regressor bootstraping scheme, which shows that Andrewsf tabulated critical values for the test statistics are oversized, and are not robust to the presence of nonstationarities in the marginal distribution of the regressors. In search of alternative bootstraping schemes, we experiment with the sieve, wild, and Rademacher schemes to ascertain if there are any possible improvements over the fixed-regressor scheme. Finally, we apply the methodology to test the stability and persistence of the Phillips curve in Nigeria using quarterly data on inflation and the output gap from 1960 to 2009. We find that, unlike Andrews asymptotic p-values, inference based on Hansenfs hetero-corrected bootstrap technique supports the hypothesis of a structural break in the inflation dynamics in Nigeria. One key policy implication is that, within a certain range of the output gap, the central bank could use the policy rate to stimulate demand up to a certain limit with no consequential positive impact on inflation.
Keywords: C22; E31; C15; 330; Bootstrapping; Phillips curve; structural change test; SupF